The moral economies of ethnic and nationalist claims - Berman, Bruce 1942-; Laliberté, André 1959-; Larin, Stephen J. 1977- (UBC Press, 2016)
"This argues that the forces of globalization have fostered competing moral economies, leading to increased ethnic and nationalist conflict. Bringing together international experts on ethnicity and governance, this book investigates how economic justice and reciprocity--the normative principles at the core of a moral economy--have become recast in identity-based communities in ways that precipitate or exacerbate such conflicts. Its combination of theoretical chapters and case studies--ranging from Africa and Asia to North America--provide compelling evidence for the value of moral economy analysis in understanding and preventing problems associated with ethnic and nationalist mobilization."--
Keywords: Ethik; Nationalismus; Politik; Wirtschaft; Ethnizität; Wirtschaftsethik; Economics / Moral and ethical aspects; Ethnic relations; Economics / Political aspects; Nationalism; Aufsatzsammlung